Institutionalizing Educational Reform: Balancing Tradition and Modernity at Pesantren - Malisi, M. Ali Sibram; Sulasman, Sulasman; Mohad, Abd Hakim (Jurnal Pendidikan Islam, 2024)
The educational reform of Rasyidiyah Khalidiyah Islamic Boarding School (RKIBS) has played a transformative role in shaping the social and economic dynamics of the Amuntai community in South Kalimantan. This study investigates the reform's impacts on the traditionally rooted Amuntai society using a socio-historical method that integrates historical and sociological perspectives. The findings demonstrate that RKIBS fulfills four critical functions: transmitting Islamic knowledge, preserving Islamic traditions, developing intellectual scholars, and driving socioeconomic progress. These roles underscore the school's influence not only as an educational institution but also as a catalyst for broader community development. By blending traditional values with modern advancements, RKIBS has significantly contributed to the intellectual growth and economic empowerment of the Amuntai society. The study concludes by emphasizing the broader implications of educational reform in balancing cultural preservation and progressive change, positioning RKIBS as a model for fostering intellectual and socioeconomic advancement in similar communities. This case study provides valuable insights into the potential of Islamic boarding schools to serve as agents of sustainable development while maintaining their cultural and religious heritage.